Stress Coping in Nurses at Naimata Psychiatric Hospital Kupang - Namo, Janwar Daud; Lerik, Mariana Dinah Charlota; Doke, Soni (Media Kesehatan Masyarakat, 2023)
Nurses are at risk of stress due to having important duties in health services; therefore, stress coping is very important to maintain mental health and workability. The study was to determine the coping mechanism of stress based on age, gender, level of education, and length of service in nurses at Naimata Psychiatric Hospital. This research was descriptive. The population included all nurses of 75 people. The sample of 43 nurses was taken by applying a simple random sampling technique. The instrument used was a Likert-scale questionnaire. The results showed that 58.1% of nurses used maladaptive coping mechanisms. The age range of 26-35 years and being male tended to do maladaptive coping mechanisms for 53.5% and 34.9%, respectively. In addition, nurses with DIII and work service of <3 years were likely to do maladaptive coping mechanisms, namely 71.4% and 34.9%, respectively. Nurses need to take stress management training and access information to manage their stress.